A critique of everyday life in Michel Houellebecq's Extension du domaine de la lutte. - Willging, Jennifer (Modern & Contemporary France, 2020)
This article compares the critique of contemporary everyday life articulated in Michel Houellebecq's first novel in particular, Extension du domaine de la lutte, with that elaborated by Marxist philosopher and sociologist Henri Lefebvre throughout his long career. It demonstrates that Houellebecq's portrayal of the destructive forces of neoliberalism and consumerism is very much in line with Lefebvre's assessment of them. Paradoxically, however, Lefebvre's ideas inspired some of the leaders of the May 1968 student protests, events figured in Houellebecq's writing as precipitating the extreme individuation and dehumanisation at work in contemporary Western society. For Lefebvre, May '68 constituted what he defined as a 'moment,' a personal or collective experience of disalienation during which those who live it can envisage, if briefly, a freer and more fulfilling way of life. For Houellebecq, on the other hand, the protestors' demands for new freedoms only succeeded in destroying the last vestiges of a moral order that at least had the merit of serving as a bulwark against human isolation. If for Lefebvre contemporary men and women suffer from acute alienation in spite of May '68, for Houellebecq they do so largely because of it.